2013
DOI: 10.1186/1745-6673-8-12
|View full text |Cite
|
Sign up to set email alerts
|

The effect of introducing IGRA to screen French healthcare workers for tuberculosis and potential conclusions for the work organisation

Abstract: IntroductionIn France, pre-employment screening for tuberculosis (TB) is performed for healthcare workers (HCW). Screening is repeated when exposure to TB patients or infectious material occurs. The results of these TB screenings were analysed in a retrospective analysis.MethodTuberculin skin tests (TST) and interferon-gamma release assays (QuantiFERON® Gold In-Tube – QFT) were used to perform the TB screenings. The screening results of 637 HCWs on whom QFT was performed were taken from the records of the Univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
(29 reference statements)
1
10
1
Order By: Relevance
“…A second study in Italian healthcare students found a prevalence of positive TST of 3.8% [24] . We found a lower prevalence rate than a recent French study (22.2%) [25] and a Portuguese study (29.5%) [26] , but higher rates than two studies from Norway [27] and Denmark (3.4% and 1%) [28] , respectively. Moreover, Fong et al observed a prevalence of a positive QFT of 6.6% in the US [29] .…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…A second study in Italian healthcare students found a prevalence of positive TST of 3.8% [24] . We found a lower prevalence rate than a recent French study (22.2%) [25] and a Portuguese study (29.5%) [26] , but higher rates than two studies from Norway [27] and Denmark (3.4% and 1%) [28] , respectively. Moreover, Fong et al observed a prevalence of a positive QFT of 6.6% in the US [29] .…”
Section: Discussioncontrasting
confidence: 84%
“…In contrast to our findings, Rafiza and Rampal observed an increased risk of LTBI for workers in emergency wards [30] and Franchi et al found that TST conversion was associated with working in an obstetric emergency room and ambulatory discharge [31] . Several European HCW studies found no association between positive QFT and workplace [21] , [25] , [32] , [33] . The high rate of positive IGRA (14.2%) in administrative staff seems astonishing, but the occupational physician who was responsible for the decision about the screening saw these employees as being at a certain risk.…”
Section: Discussionmentioning
confidence: 97%
“…Nosocomial transmission of PTB is a well‐known risk for outpatients, inpatients, and health‐care workers . With the coincident advent of human immuno‐deficiency virus and multi‐drug‐resistant TB, an outbreak in high‐income country has been reported, in which more than half of exposed patients developed disease and died.…”
Section: Discussionmentioning
confidence: 99%
“…Whether QFT-GIT is an essential biomarker of preventive treatment efficacy remains controversial (Bastos et al, 2013;Cranmer et al, 2018;Goletti et al, 2018;Goletti et al, 2007;Kabeer et al, 2011;Takenami et al, 2012). In addition, the occurrence of reversion and conversion of IGRA results has been reported in cohort studies of untreated LTBI (Adams et al, 2015;Adetifa et al, 2013;Aichelburg et al, 2014;Andrews et al, 2015;Bartalesi et al, 2013;Chiappini et al, 2012;Lee et al, 2012;Monárrez-Espino et al, 2014;Moucaut et al, 2013;Shu et al, 2016;Uto et al, 2014;Zwerling et al, 2013). Hence, larger-scale trials are required to validate the use of serial QFT-GIT tests for evaluating the efficacy of preventive treatment.…”
Section: Introductionmentioning
confidence: 99%